PENGARUH CORPORATE GOVERNANCE TERHADAP KEMUNGKINAN TERJADINYA FRAUDULENT FINANCIAL REPORTING (Studi Empiris pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Saputra, Moh. Wahyu Imam; Parasetya, Mutiara Tresna (Diponegoro Journal of Accounting, 2024)
A financial report which reflects the condition and performance of the company, is used as a means of communication and a basis for decision making for stakeholders. However, management often carries out fraudulent financial reporting, resulting in information asymmetry and allowing agency problems to occur. Therefore, an effective monitoring system is needed, one of which is through the implementation of corporate governance.The independence of the board of commissioners, remuneration of the board of commissioners, financial expertise of the main director, financial expertise of the board of commissioners, frequency of board of commissioners meetings, and managerial ownership are used to see the influence of corporate governance on the possibility of fraudulent financial reporting. A total of 261 research samples will be observed using a binary logistic regression model. Based on the empirical evidence obtained, the frequency of board of commissioners meetings are proven to have a negative influence on the possibility of fraudulent financial reporting. Meanwhile, the independence of the board of commissioners, remuneration of the board of commissioners, financial expertise of the CEO, financial expertise of the board of commissioners, and managerial ownership do not have a significant influence on the possibility of fraudulent financial reporting.Considering the research results obtained, it is appropriate for companies to implement good corporate governance. Through the implementation of good corporate governance, it will indirectly increase company value in the long term. This is because stakeholders feel confident that the company's financial reports have been prepared fairly and accountably.